Ancient Dispersal of the Human Fungal Pathogen Cryptococcus gattii from the Amazon Rainforest - Hagen, Ferry; Ceresini, Paulo C. [UNESP]; Polacheck, Itzhack; Ma, Hansong; van Nieuwerburgh, Filip; Gabaldon, Toni; Kagan, Sarah; Pursall, E. Rhiannon; Hoogveld, Hans L.; van Iersel, Leo J. J.; Klau, Gunnar W.; Kelk, Steven M.; et al. (Public Library Science, 2013)
Over the past two decades, several fungal outbreaks have occurred, including the high-profile 'Vancouver Island' and 'Pacific Northwest' outbreaks, caused by Cryptococcus gattii, which has affected hundreds of otherwise healthy humans and animals. Over the same time period, C. gattii was the cause of several additional case clusters at localities outside of the tropical and subtropical climate zones where the species normally occurs. In every case, the causative agent belongs to a previously rare genotype of C. gattii called AFLP6/VGII, but the origin of the outbreak clades remains enigmatic. Here we used phylogenetic and recombination analyses, based on AFLP and multiple MLST datasets, and coalescence gene genealogy to demonstrate that these outbreaks have arisen from a highly-recombining C. gattii population in the native rainforest of Northern Brazil. Thus the modern virulent C. gattii AFLP6/VGII outbreak lineages derived from mating events in South America and then dispersed to temperate regions where they cause serious infections in humans and animals.